To organize each given equation to express P as a function of Q we will solve each equation for P.
1) Adding P to the first equation we get:
![\begin{gathered} Q+P=30-P+P, \\ Q+P=30. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y559etcjayszk1gmvr7v067pz4yo9qannm.png)
Subtracting Q to the above equation we get:
![\begin{gathered} Q+P-Q=30-Q, \\ P=30-Q\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iiiir7d3sp6ne6lhmobkbamsng5wt69qt4.png)
2) Adding 5P to the second equation we get:
![\begin{gathered} Q+5P=20-5P+5P, \\ Q+5P=20. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/to2mp2e1u5v8g1ov2gqda0zht5mf9wiloh.png)
Subtracting Q to the above equation we get:
![\begin{gathered} Q+5P-Q=20-Q, \\ 5P=20-Q\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3gq3o6biatqltp037oy6pjadpa6mki1tz1.png)
Dividing the above equation by 5 we get:
![\begin{gathered} (5P)/(5)=(20-Q)/(5), \\ P=4-(Q)/(5)\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fukse4q4pjwgoimm5riruvpsjiabmiyabn.png)
3) Adding 2P to the third equation we get:
![\begin{gathered} 6Q+2P=14-2P+2P, \\ 6Q+2P=14. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x6bkwhp88cop2cqwxs18w5z9eh44e2cdjs.png)
Subtracting 6Q to the above equation we get:
![\begin{gathered} 6Q+2P-6Q=14-6Q, \\ 2P=14-6Q\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gw4kz2eiggonc1epka7s1hzco3up2h1sig.png)
Dividing the above equation by 2 we get:
![\begin{gathered} (2P)/(2)=(14-6Q)/(2), \\ P=7-3Q\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d5xlj4xct4x203md4d96jaimvdg1vnfua5.png)
Answer:
![\begin{gathered} 1)P=30-Q, \\ 2)P=4-(Q)/(5), \\ 3)P=7-3Q\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vh25urzv3lrvizvr04zkdvcx5ikdg36s7d.png)